To solve the quadratic equation \( x^2 - 16x + 64 = 0 \) using the perfect square trinomial pattern, we recognize that the expression on the left side can be factored.
The expression \( x^2 - 16x + 64 \) can be rewritten as:
\[ (x - 8)^2 \]
This is because:
\[ (x - 8)(x - 8) = x^2 - 8x - 8x + 64 = x^2 - 16x + 64 \]
Now, substituting back into the equation, we have:
\[ (x - 8)^2 = 0 \]
Next, we take the square root of both sides:
\[ x - 8 = 0 \]
Solving for \( x \), we get:
\[ x = 8 \]
Thus, the solution to the quadratic equation \( x^2 - 16x + 64 = 0 \) is:
\[ \boxed{8} \]